Pharmacogenomics in Clinical Practice: Assessing the Collaborative Roles of Pharmacists and Laboratory Technicians in Personalized Medicine in KSA - Taiseer Hammad R Almutiri; Ibrahim Mudayni M Alshuqaybi; Husain Ali Mohammed Humrani; Menwer Tashan Zayed Alanazi; Rashed Abdullah Nasser Almutairi (International Journal of Medical Toxicology and Legal Medicine, 2024)
Pharmacogenomics, the study of how an individual’s genetic makeup influences their response to medications, holds immense potential for advancing personalized medicine. In the Kingdom of Saudi Arabia (KSA), the implementation of pharmacogenomics in clinical practice is an emerging field that requires collaboration among healthcare professionals. This paper explores the roles of pharmacists and laboratory technicians in the successful integration of pharmacogenomics into patient care in KSA. A comprehensive literature review was conducted to assess the current state of pharmacogenomics in KSA, the roles and responsibilities of pharmacists and laboratory technicians, and the challenges and opportunities for collaboration. The findings reveal that pharmacists play a crucial role in interpreting pharmacogenomic test results, providing patient education, and making personalized medication recommendations. Laboratory technicians, on the other hand, are responsible for accurately performing pharmacogenomic tests and ensuring quality control. Effective collaboration between these two professions is essential for the successful implementation of pharmacogenomics in clinical practice. However, several barriers to collaboration exist, including a lack of standardized protocols, limited education and training, and inadequate infrastructure. To overcome these challenges, the paper proposes recommendations for enhancing collaboration, such as establishing multidisciplinary teams, providing targeted education and training, and developing standardized guidelines. By fostering collaboration between pharmacists and laboratory technicians, KSA can harness the full potential of pharmacogenomics to improve patient outcomes and advance personalized medicine.